SERCA2a ameliorates cardiomyocyte T-tubule remodeling via the calpain/JPH2 pathway to improve cardiac function in myocardial ischemia/reperfusion mice - Shuai Wang (Nature Portfolio, 2021)
Abstract Transverse-tubules (T-tubules) play pivotal roles in Ca2+-induced, Ca2+ release and excitation–contraction coupling in cardiomyocytes. The purpose of this study was to uncover mechanisms where sarco/endoplasmic reticulum Ca2+ ATPase (SERCA2a) improved cardiac function through T-tubule regulation during myocardial ischemia/reperfusion (I/R). SERCA2a protein expression, cytoplasmic [Ca2+]i, calpain activity, junctophilin-2 (JPH2) protein expression and intracellular localization, cardiomyocyte T-tubules, contractility and calcium transients in single cardiomyocytes and in vivo cardiac functions were all examined after SERCA2a knockout and overexpression, and Calpain inhibitor PD150606 (PD) pretreatment, following myocardial I/R. This comprehensive approach was adopted to clarify SERCA2a mechanisms in improving cardiac function in mice. Calpain was activated during myocardial I/R, and led to the proteolytic cleavage of JPH2. This altered the T-tubule network, the contraction function/calcium transients in cardiomyocytes and in vivo cardiac functions. During myocardial I/R, PD pretreatment upregulated JPH2 expression and restored it to its intracellular location, repaired the T-tubule network, and contraction function/calcium transients of cardiomyocytes and cardiac functions in vivo. SERCA2a suppressed calpain activity via [Ca2+]i, and ameliorated these key indices. Our results suggest that SERCA2a ameliorates cardiomyocyte T-tubule remodeling via the calpain/JPH2 pathway, thereby improving cardiac function in myocardial I/R mice.